When Time Binds: Returns to Working Long Hours and the Gender Wage Gap among the Highly Skilled - Patricia Cortes; Jessica Pan (Institute for the Study of Labor (IZA), 2016)
This paper explores the relationship between gender differences in hours worked, the returns to working long hours, and the gender pay gap among highly educated workers. Using a cross-section of occupations, Goldin (2014) documents that occupations characterized by high returns to overwork are also those with the largest gender gap in earnings. To provide a causal link between the demand for long hours and how it relates to gender wage gaps, we exploit supply side shocks – generated by intercity variation in low-skilled immigrant flows – to examine whether reductions in the cost of supplying longer hours of work allow women to close the gap in hours of work and benefit from higher wages. We find that low-skilled immigration leads to a reduction in a city's gender gap in overwork, as well as in the gender pay gap in occupations that disproportionately reward longer hours of work.
Keywords: J16; J22; 330; gender wage gap; long hours; overwork; low-skilled immigration